Smashing barriers: Strengthening supportive social network communication for disabled small to medium-sized enterprises - Ibrahim, Fachmi; P. Lubis, Djuara; Muljono, Pudji; Sadono, Dwi (Jurnal Komunikasi, 2026)
This study explores how communication within social networks mediates access to resources and entrepreneurial success among people with disabilities. Moving beyond resource-based perspectives that emphasize financial capital, the research applies a communicative–relational framework integrating social capital theory and communication theory of resilience. The study adopts a mixed-methods approach using the Analytic Hierarchy Process with five expert informants to identify and prioritize key factors affecting business performance among disabled micro-entrepreneurs in Indonesia. Results reveal that while financial resources remain foundational, their impact depends heavily on communicative linkages across disability support organizations, mentorship structures, and community networks. Social network communication serves as a mediating mechanism that converts tangible resources into adaptive capacity, innovation, and social recognition. The findings underscore the need for inclusive entrepreneurship programs that enhance both resource accessibility and communicative competence, positioning communication as a form of social capital essential for sustainable development.